2020
DOI: 10.1055/s-0040-1713133
|View full text |Cite
|
Sign up to set email alerts
|

Attributing Patients to Pediatric Residents Using Electronic Health Record Features Augmented with Audit Logs

Abstract: Objective Patient attribution, or the process of attributing patient-level metrics to specific providers, attempts to capture real-life provider–patient interactions (PPI). Attribution holds wide-ranging importance, particularly for outcomes in graduate medical education, but remains a challenge. We developed and validated an algorithm using EHR data to identify pediatric resident PPIs (rPPIs). Methods We prospectively surveyed residents in three care settings to collect self-reported rPPIs. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“… 11 Aims were not mutually exclusive so each study could have more than 1 aim. While all vendor-measure studies measured an amount of EHR use (e.g., volume or duration), 2–4 , 6 , 19 , 24–58 a third (33%) of investigator-measure studies did not, 60 , 68 , 74 , 78 , 80 , 82–87 , 89 , 91 , 92 , 98 , 102 , 109 , 112 , 115 focusing instead on the other 2 aims ( P < .001). Vendor-measure studies were more likely to characterize EHR or clinical workflows , such as when EHR activities were performed during the day (68% vs 43% of articles, P = .016), while investigator-measure studies were more likely to characterize team dynamics , for example, using record coaccess to determine which clinicians routinely worked together (23% vs 3% of studies, P = .004).…”
Section: Resultsmentioning
confidence: 99%
“… 11 Aims were not mutually exclusive so each study could have more than 1 aim. While all vendor-measure studies measured an amount of EHR use (e.g., volume or duration), 2–4 , 6 , 19 , 24–58 a third (33%) of investigator-measure studies did not, 60 , 68 , 74 , 78 , 80 , 82–87 , 89 , 91 , 92 , 98 , 102 , 109 , 112 , 115 focusing instead on the other 2 aims ( P < .001). Vendor-measure studies were more likely to characterize EHR or clinical workflows , such as when EHR activities were performed during the day (68% vs 43% of articles, P = .016), while investigator-measure studies were more likely to characterize team dynamics , for example, using record coaccess to determine which clinicians routinely worked together (23% vs 3% of studies, P = .004).…”
Section: Resultsmentioning
confidence: 99%
“…Because residents may not be the physician signing the note, this metric serves as a proxy measure of productivity and may not capture some patients who may be seen by resident physicians who do not sign the chart note. 33 Further, patients seen per day in an ambulatory setting may not be a good measure of resident productivity for a variety of reasons mentioned above, most specifically that resident physicians may not be in control of their workloads.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have described barriers in developing dashboards for use by trainees, including challenges with patient attribution which can lead trainees to feel that metrics are not as meaningful. 5,[25][26][27][28] In our study, resident users seemed overall to understand the limitations of the dashboard, but similarly reported that some metrics were less meaningful on an individual basis due to patient attribution limitations. Resident comments indicated that they felt some metrics were more reflective of decisions made by the care team rather than an individual, which is consistent with findings of other studies regarding the challenges of creating resident-specific performance metrics.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, our patient attribution was based exclusively on note writing, which may not perfectly reflect all patients cared for by a resident. 25,28 A resident may have participated meaningfully in the care of a patient, but if no note was written (for example, if care occurred overnight) then this would not be captured by the dashboard. Additionally, at our institution upper-level residents (PGY2 and above) typically sign fewer notes than interns on this rotation, which makes the results of some parts of the dashboard less relevant as residents advance in their training.…”
Section: Limitationsmentioning
confidence: 99%